Indoor thermal comfort in academic building of MRSM Parit: towards student’s satisfaction and perceived performance / Nurul Azreen Azmi - Azmi, Nurul Azreen (2022)
Thermal comfort in a classroom is crucial and significantly important in a students’ life as it may affect the learning process as well as the academic achievement. Students spend most of their time at school and in class. Therefore, the thermal comfort in the classroom must be considered carefully because of the high negative influence that an unsatisfactorily thermal environment may have on learning and students’ performance. This study aims to evaluate indoor thermal comfort in the academic building of MRSM Parit towards student’s satisfaction and perceived performance. Hence, the first objective of the study is to measure the thermal comfort performance of the classroom. This was achieved through fieldwork measurement in three classes for three weeks where four parameters of thermal comfort were measured during lesson hours. The second objective is to identify students’ satisfaction and students’ perceived performance towards the indoor thermal comfort of their classroom. This objective was achieved through survey measurement which is distribution of questionnaires. A five-point Likert scale questionnaire was distributed using Google Form, that act as a data collection tool since the distribution and filling out was conducted online. 289 students, age between 14 to 17 years old completed the survey. Data from each method was analysed, tabulated, and graphed by using SPSS Statistic Version 26.0 and Microsoft Excel.